2020
DOI: 10.33508/jako.v12i1.2211
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen laba riil dan keterbacaan laporan tahunan

Abstract: This study aims to empirically examine the relationship between real earnings management and the company's annual report readability. The population of this research is all companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 by excluding the financial sector. The sampling technique used was purposive sampling. Data analysis was performed using multiple linear regression with the IBM 25.0 SPSS program. The test results show that real earnings management as measured by abnormal discretional expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
1
0
3
Order By: Relevance
“…This result is in line with the studies conducted earlier by Ajina et al (2016) and Lo et al (2017). Furthermore, this is supported by the latest research from Abshari and Rahman (2020), who examined the effect of real earnings management on the readability of annual reports and found that there is a management motive in presenting annual reports. Further, testing in Model 2 as indicated in Table 4 regarding the moderating effect of female directors on the board of commissioners toward earnings management and annual report readability was not successful.…”
Section: Resultssupporting
confidence: 90%
“…This result is in line with the studies conducted earlier by Ajina et al (2016) and Lo et al (2017). Furthermore, this is supported by the latest research from Abshari and Rahman (2020), who examined the effect of real earnings management on the readability of annual reports and found that there is a management motive in presenting annual reports. Further, testing in Model 2 as indicated in Table 4 regarding the moderating effect of female directors on the board of commissioners toward earnings management and annual report readability was not successful.…”
Section: Resultssupporting
confidence: 90%
“…1.345,8 Juta yang diputus oleh Hakim dan Rp. 101,7 Juta yang dibayar oleh pelaku (LPSK, 2020). Penghitungan restitusi tersebut dilakukan terhadap 4 (empat) jenis tindak pidana yaitu kekerasan seksual, perdagangan orang, penganiayaan berat dan tindak pidana umum lainnya (terdiri dari peristiwa pembunuhan, penyiksaan, kekerasan dalam rumah tangga dan kekerasan terhadap anak) (LPSK, 2020).…”
Section: Pendahuluanunclassified
“…Penghitungan restitusi tersebut dilakukan terhadap 4 (empat) jenis tindak pidana yaitu kekerasan seksual, perdagangan orang, penganiayaan berat dan tindak pidana umum lainnya (terdiri dari peristiwa pembunuhan, penyiksaan, kekerasan dalam rumah tangga dan kekerasan terhadap anak) (LPSK, 2020). Rendahnya pemenuhan hak restitusi kepada korban pada proses peradilan, disebabkan oleh : 1) penghitungan restitusi tidak masuk ke dalam tuntutan Jaksa Penuntut Umum (JPU) dengan alasan tidak memiliki dasar hukum untuk menuntut restitusi kepada terdakwa dan mengetahui ketidakmampuan terdakwa dalam membayar restitusi kepada korban atau terdakwa; 2) penghitungan restitusi tidak dikabulkan hakim karena hakim tidak mendalami kerugian yang dialami korban, tidak memiliki perspektif korban dan menilai terdakwa tidak memiliki kemampuan membayar restitusi; dan 3) proses hukum berhenti atau dihentikan, namun berkas tuntutan restitusi sudah masuk ke penyidik/JPU (LPSK, 2020). Terlihat masih ada tantangan dalam upaya peningkatan pemahaman Aparatur Penegak Hukum (APH) tentang pentingnya upaya pemulihan bagi korban tindak pidana terlepas dari adanya alasan ketidakmampuan pelaku/terdakwa untuk membayar restitusi.…”
Section: Pendahuluanunclassified
“…Berdasarkan data Badan Pengawas Obat dan Makanan (BPOM) nasional tahun 2019 dari sampel Pangan Jajanan Anak Sekolah (PJAS) yang tidak memenuhi syarat sebanyak 20,10% 3 . Hasil laporan tahunan BPOM Sulawesi Tenggara tahun 2020 menyatakan dari 261 sampel makanan yang diuji, diperoleh sebanyak 226 sampel memenuhi syarat dan 35 sampel tidak memenuhi syarat karena mengandung bahan pemanis buatan, pengawet, boraks, formalin dan cemaran logam 4.…”
Section: Pendahuluanunclassified